Перші карти українських земель з політико-адміністративним поділом - Сосса, Р. (Історико-географічні дослідження в Україні, 2019)
Перші карти українських земель з політико-адміністративним поділом. Розглянуто перші карти українських земель із зображенням політико-адміністративного розмежування. Проведено докладний аналіз територіального розмежування
українських земель на картах в атласах А. Ортелія і Ґ. Меркатора. Виявлено
численні неточності у проходженні кордонів і меж, у назвах адміністративних одиниць. Звернено увагу на способи зображення кордонів й адміністративних меж. The author highlights the first maps of the Ukrainian territories as parts of different
states with the political and administrative division marked. These maps were issued in
16th century.
The author also highlights how the state and administrative borders at the Ukrainian
lands are shown on “The Southern Sarmatia” map by Polisk cartographer B.Vapovsky
(1526) and on the wall map of the Europe by Dutch cartographer G. Mercator (1554). It
is also some maps by M. Waldseemüller, S. Münster, D. Gastaldi, on which the names
of some administrative parts are written, are mentioned.
A detailed analysis of the territorial delineation of Ukrainian lands on maps in
the atlases A. Orteliya (maps of Poland V. Grodetsky and A. Pograbki), on maps of
Lithuania and Tavrika of Chersonesos in atlases of G. Mercator, including their numerous
subsequent editions. Many inaccuracies were detected both in the passage of borders
and administrative boundaries, and in the names of administrative units in the Ukrainian
territories. Attention is drawn to the ways in which borders and administrative boundaries
are portrayed, their symbolic designations. To display the state boundaries and the
voivodships, one common symbol was used - a line from points or from small triangles.
The author found out that the mapping of the political and administrative division of
territories on maps in 16th century was not in the focus of the cartographers. The new
editions of the maps and atlases did not include the up to date information about changes
in this sphere, they could be issued without changes for decades. Maps publishers often
copied inaccurate and unchecked information from each other. This led to multiplying
the numerous mistakes and inaccuracies. Such works can not be used as cartographic
sources for mapping historical themes.